Educational possibilities of wiki - Mora-Vicarioli, Francisco (2012)
The article presents the use of wiki as a flexible tool that provides great opportunities for education. The main feature of this resource is that it allows a set of users to interact asynchronously to create some content and everyone can add, remove or edit the contributions from themselves or others.